Lactitol may improve the prognosis of hepatocellular carcinoma through the proliferation of Megasphaera as well as Bifidobacterium - Abiru, Seigo; Kugiyama, Yuki; Suehiro, Tomoyuki; Motoyoshi, Yasuhide; Saeki, Akira; Nagaoka, Shinya; Yamasaki, Kazumi; Komori, Atsumasa; Yatsuhashi, Hiroshi (Frontiers in Medicine, 2025)
BackgroundIncreasing evidence suggests that gut microbiota and their metabolites can modulate antitumor immunity. However, sufficient evidence from human studies is lacking. We evaluated the association of lactitol and lactulose as prebiotics with the progression of hepatocellular carcinoma (HCC).MethodsIn Study 1, the effects of lactitol and lactulose on overall survival (OS) of patients with HCC with Child-Pugh scores of B or C were investigated in patients diagnosed at the Nagasaki Medical Center between 2003 and 2020. In Study 2, the effects of these substances on the gut microbiota of patients with cirrhosis were analyzed. Study 3 examined the effect of these substances on serum albumin levels in patients with cirrhosis.ResultsIn Study 1, a total of 321 patients were evaluated, and 55 pairs of Lactitol and Non-Lactitol groups and 80 pairs of Lactulose and Non-Lactulose groups were created using one to one propensity score matching. The Lactitol group showed a significant improvement (p < 0.05) in OS compared to the Non-Lactitol group, but the Lactulose group did not show any significance compared to the Non-Lactulose group. In Study 2, the number of Bifidobacterium was higher in the Lactitol group and the Lactulose group than in the Control group, but the number of Megasphaera was significantly higher only in the Lactitol group. In addition, in a study of 10 cases in which the gut microbiota was examined before and after lactitol use, an increase in Bifidobacterium and Megasphaera was observed after lactitol use. Study 3 found that lactitol had no beneficial effect on serum albumin levels.ConclusionLactitol may improve the prognosis of HCC through the proliferation of Megasphaera as well as Bifidobacterium.